Evaluation of the impact of the state of emergency during the COVID-19 pandemic on childhood immunizations in Benguela Province, Angola - Tadatsugu Imamura; Keiji Mochida; Balogun Olukunmi; Lino Tchicondingosse; Pedro Sapalalo; Ketha Rubuz Francisco; Ai Aoki; Akira Ishiguro; Kenji Takehara (Tropical Medicine and Health)
Abstract Background The impact of public health measures against the coronavirus disease 2019 on the rate of childhood immunization has not yet been fully defined. Particularly, measures which directly affect health-seeking behaviors (e.g., the State of Emergency; SoE) drew public health attention. We aim to describe this impact in Benguela Province, Angola, by comparing the immunization rates between infants who had their immunizations before and after the SoE, which was declared on March 27, 2020. Methods We retrospectively reviewed the epidemiological data of infants born between November 2019 and February 2020 in Benguela Province, Angola. Immunization rates (i.e., the number of immunized infants divided by the number of infants in the group of same months of birth and residential areas) were calculated for 11 vaccines that infants received from at birth to the 4th month after birth. The rates for the 2nd month vaccines were compared between infants immunized before the SoE (post-SoE), and after the SoE (pre-SoE). Results Among 9,595 infants, the overall immunization rates were higher in the post-SoE (71.9–77.8%) than in the pre-SoE groups (66.0–73.8%). The overall immunization rates were higher in the post-SoE group than in the pre-SoE group in both urban and rural municipalities, although the rates were > 20% higher in urban than in rural municipalities. The immunization rates in the recommended month showed a similar trend, except for the stratified analysis for rural municipalities, where the rates were 2.3–4.1% lower in the post-SoE than in the pre-SoE groups. The most common reason for missing immunization was vaccine unavailability at health units (19.9%, 684/3,440). Less than 10% of missed immunizations were due to the SoE, which occurred mostly in infants born in rural municipalities in February 2020 (9.8%, 52/532). Less than 2% of missed immunizations were due to health units not being open, and was highest in rural municipalities in January 2020 (1.6%, 27/1,673). Conclusions Our study suggested that the disruptive impacts of public health measures against pandemics on rates of childhood immunization can be mitigated, and support is needed for areas with vulnerable health systems, such as rural areas.